1996
DOI: 10.1148/radiology.201.1.8816555
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline cartilage: truncation artifact as a cause of trilaminar appearance with fat-suppressed three-dimensional spoiled gradient-recalled sequences.

Abstract: The trilaminar appearance depicted within hyaline cartilage on MR images obtained with this sequence is predominantly attributable to truncation artifact rather than to histologic zonal anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 0 publications
1
33
0
2
Order By: Relevance
“…A laminated appearance of the articular cartilage is commonly seen on MR imaging. This laminar appearance within the articular cartilage on FS 3D GE images is predominantly attributable to truncation artefact due to under-sampling of the high spatial frequencies rather than to histological zonal anatomy (Figure 4) (Erickson et al 1996, Frank et al 1997, Waldschmidt et al 1997. The current author has reported this laminated appearance in growth plate cartilage in rats ( Figure 5, Wang et al 2006b).…”
Section: Imaging Artefactsmentioning
confidence: 70%
“…A laminated appearance of the articular cartilage is commonly seen on MR imaging. This laminar appearance within the articular cartilage on FS 3D GE images is predominantly attributable to truncation artefact due to under-sampling of the high spatial frequencies rather than to histological zonal anatomy (Figure 4) (Erickson et al 1996, Frank et al 1997, Waldschmidt et al 1997. The current author has reported this laminated appearance in growth plate cartilage in rats ( Figure 5, Wang et al 2006b).…”
Section: Imaging Artefactsmentioning
confidence: 70%
“…In other studies, high-resolution MR images of articular cartilage revealed a multilaminar appearance reflecting distinct anatomical zones, but it was also reported that a false laminar appearance can be created by MR imaging truncation artifacts from opposing cartilage edges (8,9). Different T2 relaxation times have also been measured as a function of cartilage depth.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, these sequences seemed to provide biochemical information of AC. This was based on the observation that the laminar appearance of AC correlated with layers that differed in proteoglycan (PG) contents [16], although other investigators have questioned the laminar appearance of AC on 3-D SPGR and rather attributed the changes in signal intensity to technical artifacts [3,4]. These previous observations, however, cannot be directly applied to companion animals since most of the studies have been performed on the knee AC, which is easy to obtain high quality images on MRI because of its location and thickness.…”
mentioning
confidence: 99%